Minimizing Plagiarism of Undergraduate Students’ Thesis Proposal by Using Quillbot Paraphraser - Wahyuni, Sri; Dollah, Syarifuddin; Amin, Fatimah Hidayahni (Yayasan Ahmar Cendekia Indonesia, 2025)
This qualitative study investigates how undergraduate students use the QuillBot Paraphraser to minimize plagiarism in the process of writing their thesis proposals. Conducted in December 2024 at the English Education Department of STKIP YPUP Makassar, the research employed purposive sampling to select five students who were actively working on their proposals and had prior experience using QuillBot. Data were collected through semi-structured interviews and supported by document analysis using Turnitin plagiarism reports. The findings revealed that students generally follow a structured paraphrasing process. Students reported significant improvements in sentence structure, vocabulary use, and a noticeable reduction in similarity percentages on Turnitin. The study concludes that QuillBot can effectively support the minimization of plagiarism and improvement of academic writing quality.